Mismatch in preferences for working from home: Evidence from discrete choice experiments with workers and employers - Piotr Lewandowski; Katarzyna Lipowska; Mateusz Smoter (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
We study preferences for remote work using a large-scale discrete choice study with 10,000 workers and 1,500 employers in Poland. Workers value remote work more than employers. On average, workers are willing to sacrifice 2.9% of earnings for remote work, with hybrid work from home (WFH) for 2-3 days (5.1%) preferred over 5 days (0.6%). Employers expect a 21.0% wage cut from remote workers. This 18 pp gap between employers' and workers' valuations reflects employers' concerns over productivity loss (14 pp) and effort to manage remote workers (4 pp). Only 25-36% of employers with positive perceptions of remote work productivity show valuations of remote work that align with workers' willingness to pay for it. – – Wir untersuchen die Präferenzen für Remote-Arbeit anhand einer groß angelegten diskreten Wahlstudie mit 10.000 Arbeitnehmern und 1.500 Arbeitgebern in Polen. Arbeitnehmer schätzen Remote-Arbeit mehr als Arbeitgeber. Im Durchschnitt sind Arbeitnehmer bereit, 2,9 Prozent ihres Einkommens für Remote-Arbeit zu opfern, wobei sie hybride Heimarbeit für 2-3 Tage (5,1 Prozent) gegenüber 5 Tagen (0,6 Prozent) vorziehen. Arbeitgeber erwarten eine Lohnkürzung von 21 Prozent Lohneinbußen von Beschäftigten in Remote-Arbeit. Dieser Unterschied von 18 Prozentpunkten zwischen den Einschätzungen der Arbeitgeber und der Arbeitnehmer spiegelt die Bedenken der Arbeitgeber über Produktivitätsverluste (14 Prozentpunkte) und den Aufwand für die Verwaltung von Mitarbeitern in Remote-Arbeit (4 Prozentpunkte) wider. Nur 25-36 % der Arbeitgeber, die die Produktivität der Remote-Arbeit positiv einschätzen, bewerten die Remote-Arbeit so, dass sie mit der Bereitschaft der Arbeitnehmer übereinstimmt, für sie zu bezahlen.
Keywords: J21; J31; J81; 330; Working from home; remote work; discrete choice experiment; willingness to pay